Social Capital and Household Willingness to Pay for Improved Household Waste Management: A Contingent Valuation Method - Saptutyningsih Endah; Amalia Intan (E3S Web of Conferences)
Sustainability in environmental practices depend on better household waste management, and environmental policy planning needs to take into account the variables affecting residents’ willingness to pay (WTP) for waste management. This research aims to measure the amount of WTP to improve waste management at Tasikmalaya, Indonesia. With the goal of improving home waste management, this study explores how residents’ WTP is shaped by social capital, a multifaceted notion that includes social networks and trust as well as the socio-demographic aspects. To calculate residents’ WTP for waste management, the study used the contingent valuation technique (CVM). We investigated the effects of social capital on residents’ willingness to engage using a logistic regression mode. According to the findings, 64% of residents were prepared to make a monetary contribution toward the waste management process. The research results show that the WTP value is “IDR 16,500”. The important role that social capital plays in influencing WTP in the context of better household waste management is highlighted by this study’s result. By taking social capital’s effects and dimensions into account, it offers policymakers important insights for creating waste management policies that work better. This research contributes to the literature by highlighting the environmental and health risks of pollution caused by landfill.